2018
DOI: 10.3892/or.2018.6431
|View full text |Cite
|
Sign up to set email alerts
|

Morusin suppresses A549 cell migration and induces cell apoptosis by downregulating the expression of COX‑2 and VEGF genes

Abstract: The present study aimed to examine the inhibitory effects of morusin on the human lung cancer cell line A549. Various doses of morusin were applied to A549 cells and the effects were assessed by wound‑healing and MTT assays, flow cytometry analysis of apoptosis, a mitochondrial membrane potential assay and RT‑PCR. The results indicated that the concentrations of 10 and 30 µg/ml morusin significantly inhibited A549 cells and signs of apoptosis were observed. In addition, the wound‑healing assay results revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“… Classification, food sources, and chemical structure of flavonoids [ 4 , 10 , 34 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. …”
Section: Figurementioning
confidence: 99%
“… Classification, food sources, and chemical structure of flavonoids [ 4 , 10 , 34 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 ]. …”
Section: Figurementioning
confidence: 99%
“…Our previous report demonstrated that Morus alba L. inhibited the TARC/CCL17 release in tumor necrosis factor-α (TNF-α) and interferon-γ (IFN-γ)-stimulated HaCaT keratinocytes, and suppressed the development of atopic dermatitis-like lesions induced by the house dust mite in NC/Nga mice [18]. It is reported that morusin, one of the marker compounds contained in M. alba L., has an anti-tumorigenic effect in gastric [19], lung [20], hepatocellular [21], breast [22], and prostate cancer [23]. Kuwanon G, another marker compound contained in M. alba L., has been reported to have anti-atherosclerosis [24] and anti-asthma [25] effects, as well as anti-bacterial activity against oral pathogens [26].…”
Section: Introductionmentioning
confidence: 99%
“…Consistently, STAT3 target genes, such as anti-apoptotic genes encoding Bcl-xL, Bcl-2, XIAP, survivin and cell cycle regulators (c-Myc and cyclin D), are down-regulated upon morusin treatment, while pro-apoptotic Bax expression was induced [ 36 , 38 , 40 , 47 , 51 ]. In addition, the administration of morusin reduces mitochondrial membrane potential resulting in the release of cytochrome c and Smac/DIABLO and thus, apoptosis is facilitated by the activation of caspase-9 and caspase-3 [ 35 , 48 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Following the report that morusin effectively inhibits the growth of tumors in mice transplanted with H22 liver tumor cells [ 46 ], similar inhibitory effects of morusin on tumor xenografts were observed for liver, ovary, breast, kidney and gastric cancer cells [ 37 , 47 , 54 , 65 , 90 ]. In addition to inhibitory effects on tumor growth, tube formation of human umbilical vein endothelial cells (HUVEC) and expression of angiogenesis-related genes were also inhibited by morusin treatment in vitro [ 47 , 52 ], suggesting the anti-metastatic potential of morusin.…”
Section: Resultsmentioning
confidence: 99%